Is Age a Case for Electoral Quotas? A Benchmark for Affirmative Action in Politics. Issue 2 (2nd July 2016) - Trantidis, Aris
Abstract : Is age a suitable case for electoral quotas on the same grounds invoked for women in politics? If affirmative action should not be arbitrarily applied to a few social groups, we must specify the conditions that could serve as a benchmark which a group must pass in order to qualify for its application. Drawing from the literature on women in politics, this article sets up empirical indicators to examine the political under-representation of younger and older age groups: whether the age-related pattern of political under-representation is linked to stereotypes and bias that negatively affect its engagement in politics, and whether these age groups face special issues that give them a unique perspective, which only those who directly experience them can fully advocate in decision-making fora. Affirmative action raises questions about the boundaries of identity, the limits of politics as a vehicle for social change and the meaning of electoral choice.